Prediction of Phase-Inversion Temperature of a Triglyceride Microemulsion Using Design of Experiments - Jeirani, Z.; Mohamed Jan, B.; Si Ali, B.; Noor, I.M.; See, C.H.; Saphanuchart, W. (American Chemical Society, 2013)
This paper presents the estimation of phase inversion temperature (PIT) of a nonionic microemulsion by studying its interfacial tension (IFT) as a function of temperature. In this work, one-factor design (OFD), which is an approach of Design of Experiments (DOE), was used to model the variation of IFT with temperature. A transformed quadratic equation with lambda of 0.87 was then fitted and validated. The model was optimized to predict the PIT, the temperature at which the IFT is a minimum. The IFT from the optimization of the model at the predicted PIT of 44.43 °C is 0.000154709 mN/m. The value shows an excellent agreement with the experimental value (0.00018 mN/m). Therefore, DOE is capable of predicting the PIT of a microemulsion with high accuracy using only seven design points.